Mortality and Early Feeding Behavior of Female Turkey Poults During the First Week of Life - Roehrig, Colleen; Torrey, Stephanie (Frontiers in Veterinary Science, 2019)
Turkey poults are susceptible to early mortality and poor initial feeding behavior for reasons that are not well understood. This study was conducted to investigate the relationship between the development of turkey poult feeding behavior and early mortality, with a focus on the effect of biological age and diet. We hypothesized that increasing biological age would increase mortality, and that poults that had earlier feeding behavior would have decreased mortality. Nine hundred and sixty female turkey poults were randomly assigned to 24 pens (40 poults per pen). The study was conducted as a completely randomized block design with a factorial arrangement of two ages (early and standard hatch) and three diets (control, modified A, and modified Ca/P B, differing primarily in the Ca/P ratio and percent fines). The behavior during the first 24 hr after placement of newly placed poults was examined. Growth performance and mortality throughout the first week of life was also measured to determine if early behavior had any impact on these variables over time. Behavior during the first 24 hr was similar between the age treatments; both spent approximately 2.5% of the time drinking, 7% of the time feeding, 12% of the time active and 80% of the time inactive/resting. There was no effect of diet or age treatment on latency to feed or drink. Growth variables were not affected by biological age. However, there was a significant diet and biological age effect on bodyweight and mortality. Standard hatch poults fed a control diet were lighter than other poults at 7 d, while standard hatch poults fed the diet with the lowest Ca:P had the highest mortality. For all treatments, early mortality was primarily due to yolk sac infection, although greater than 1% of placed poults died due to starvation. Findings of the present study indicate that, regardless of biological age or diet, poults established feeding behavior within the first 24 hr and the majority of early poult mortality under these experimental conditions was due to factors other than starvation.